AN INTRODUCTION TO THE POST-CRITICAL BELIEF SCALE: INTERNAL STRUCTURE AND EXTERNAL RELATIONSHIPS - Duriez, Bart; Dezutter, Jessie; Neyrinck, Bart; Hutsebaut, Dirk (Psyke & Logos, 2007)
Recently, Fontaine, Duriez, Luyten and Hutsebaut (2003) have shown that the Post-Critical Belief Scale (PCBS; Duriez, Fontaine & Hutsebaut, 2000) captures the two orthogonal bipolar dimensions of Exclusion versus Inclusion of Transcendence and Literal versus Symbolic along which Wulff (1991, 1997) organized the various possible approaches to religion. This chapter outlines the original and valuable contribution of the PCBS to the field of the psychology of religion by showing how the PCBS sheds a new light on several hotly debated topics within he psychology of religion.